The Logic of Appearance: Dennett, Phenomenology and Psychoanalysis - Feyaerts, Jasper; Vanheule, Stijn (Frontiers in Psychology, 2017)
In the present essay, we aim to develop and contrast three different positions towards Sellars’ distinction between the manifest and scientific images of man: Dennett’s philosophical reconstruction of neurocognitive science, contemporary phenomenology and psychoanalysis. We will suggest that these respective traditions and the substantial differences between them can be understood in terms of a ‘logic of appearance’. Related to this are differing ideas about the rights and limits of the first-person perspective, the relation between conscious experience and belief, and the issue of naturalization. In the final part, we will try to specify, on the basis of a detailed reading of the disagreement between Dennett and phenomenology, in what way psychoanalytic theory could respond to these different issues.